Islam and Local Culture: The Acculturation Formed by Walisongo in Indonesia - Akhmad Jazuli Afandi (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This article explores the dynamic interaction between Islam and local cultures in Indonesia, focusing on the acculturation process catalyzed by the Walisongo. The historical context of Indonesia during the Walisongo period encompassed diverse local cultures, including animism, Hindu-Buddhism, and indigenous beliefs. The Walisongo adopted an inclusive approach, adapting Islamic teachings to align with local cultural norms, languages, and traditions. This study reveals how this approach facilitated the gradual spread of Islam, leading to its harmonious integration with the rich tapestry of local culture. Recognizing the significance of effective communication, the Walisongo employed local languages, arts, and customs to convey Islamic principles. This strategy forged bridges of understanding between Islam and Indonesia's varied cultures, fostering unity and inclusivity. As a result of this acculturation, unique local Islamic traditions emerged, marked by the fusion of Islamic practices with pre-existing customs and rituals. The incorporation of Islamic values into traditional cultural expressions, such as the use of the wayang kulit shadow puppet theater in Javanese culture, exemplifies this harmonious coexistence. Unlike an assimilationist approach, the Walisongo embraced cultural diversity and preserved indigenous beliefs, effectively integrating them into Islamic practices. This preservation of local identity and cultural heritage ensured that communities maintained their distinctiveness while embracing the tenets of Islam. The process of acculturation not only promoted socio-religious harmony but also established mutual respect and peaceful coexistence by accommodating local customs and beliefs. This research sheds light on the transformative impact of the Walisongo's approach in diffusing Islam across the archipelago. Their inclusive and adaptive methods resulted in a unique Indonesian Islamic identity, characterized by the harmonious interplay of Islamic values with diverse cultural expressions. As Indonesia continues to navigate its religious and cultural landscape, the Walisongo's legacy serves as a potent testament to the potential for peaceful coexistence and unity within the intricate fabric of diversity. This study offers valuable insights for contemporary scholars, policymakers, and religious leaders seeking to understand the enduring legacy of the Walisongo and the importance of embracing cultural diversity for societal cohesion and inclusivity.